The influence of different production functions on modeling resource extraction and economic growth - Frauke Voosholz (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2014)
In this paper we discuss the influence of using different production functions on modeling the resource extraction rates and economic growth. The focus is set on the modeling of the production sector, which requires either non-renewable resources, renewable resources or a combination of both resources for production. There are great differences between the possible assumptions when modeling the substitution process between the different input factors. It is shown that the existence of an optimal extraction rate in conjunction with economic growth depends on the specification of the production function even if the same parameterization is used. The target is to provide an overview on the different possibilities of modeling, and to support the decision which kind of production function should be used for modeling different aspects of economic growth.
Keywords: E23; O13; O41; O40; Q20; Q32; 330; economic growth; natural resources; production function